Needs Analysis for Classpoint-Based Interactive Media in Arabic Vocabulary Acquisition at MAN 2 Payakumbuh City - Munandar, Nilam Cahya; Rahmawati, Rahmawati; Asrina, Asrina (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The purpose of this study is to analyze the need for interactive learning media through ClassPoint in vocabulary learning in 10th grade students of State Islamic Senior High School 2 Payakumbuh City. The method used is a mixed methods, combining qualitative and quantitative approaches in one research activity. This method is intended to provide a more comprehensive picture of the need for interactive learning media based on ClassPoint in vocabulary learning. The data collection techniques include observation, interviews, and distributing questionnaires that have been validated by an expert. This study will involve 33 students of class X.E8 and 2 Arabic language teachers of class X as samples. The results of the study indicate that the learning process is still one way and does not involve interactive media that supports optimal vocabulary understanding. Based on the questionnaire, it also shows that the teacher needs analysis is 92.5% and the student needs analysis is 90%. This means that teachers and students really need interactive learning media in the learning process in the classroom. The results of the analysis show that the application of ClassPoint in Arabic vocabulary learning contributes to increasing student participation and facilitating independent learning at the public high schools.